A compact high-gain parasitic patch antenna with electronic beam-switching - D. Subramaniam; M. Jusoh; T. Sabapathy; M. N. Osman; M. R. Kamarudin; R. R. Othman; M. R. Awal (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A high beam steering antenna using HPND PIN Diode is proposed with a capability of steering its beam into three different directions -40 º, 0º and 40 º with respective switching condition. The reconfigurable parasitic antenna consists of a driven element and two reconfigurable parasitic elements, is designed with operating range of 9.5GHz. The parasitic elements act as reflectors or director depending on the switching conditions. Both parasitic elements are connected to ground plane via shorting pins. The reconfiguration is controlled by the two HPND PIN Diode switch that embeds to the parasitic element. An average gain value of 8dBi is achieved at all reconfiguration scenarios. All the simulated design has been carried out using CST software.